Quasi-linear correlation between high-frequency and static die-lectric constants in II-VI and III-V semiconductors - Daoud, Salah; Bencheikh, Abdelhalim; Belagraa, Laarbi (International Journal of Physical Research, 2016)
A quantitative form of the linear correlation between the high-frequency and static dielectric constants in ANB8-N (N = 2, 3) tetrahedrally coordinated semiconductor materials, and also in I-VII group alkali halides was studied. So, a quasi-linear relationship was found between the high-frequency and the static dielectric constants for some selected II-VI (ZnS, ZnSe, ZnTe and CdTe) and III-V (AlP, AlAs, AlSb,….etc) cubic zincblende type materials, in the other side a weak uphill linear relationship has been found in the case of I-VII (LiF, NaF, LiCl,….etc) group alkali halides compounds. In the case of II-VI and III-V cubic zincblende semiconductors, the linear regression is established with a correlation coefficient ( ) of about 0.98. The significance of the linear regression is given as the probability P <0.0001 of the null hypothesis.